2008
DOI: 10.1074/jbc.m706586200
|View full text |Cite
|
Sign up to set email alerts
|

Migration to Apoptotic “Find-me” Signals Is Mediated via the Phagocyte Receptor G2A

Abstract: Phagocytosis of apoptotic cells is fundamentally important throughout life, because non-cleared cells become secondarily necrotic and release intracellular contents, thus instigating inflammatory and autoimmune responses. Secreted "find-me" and exposed "eat-me" signals displayed by the dying cell in concert with the phagocyte receptors comprise the phagocytic synapse of apoptotic cell clearance. In this scenario, lysophospholipids (lysoPLs) are assumed to act as find-me signals for the attraction of phagocytes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
183
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 215 publications
(191 citation statements)
references
References 30 publications
8
183
0
Order By: Relevance
“…Knockdown of G2A could decrease the migratory capacity of phagocytes to apoptotic cell supernatants. 24 However, other phospholipids were also able to neutralize migration to pure LPC in a G2A-dependent manner. It is possible that a balance of different lysophospholipids released from apoptotic cells can affect migration.…”
Section: Steps Involved In Clearancementioning
confidence: 99%
See 2 more Smart Citations
“…Knockdown of G2A could decrease the migratory capacity of phagocytes to apoptotic cell supernatants. 24 However, other phospholipids were also able to neutralize migration to pure LPC in a G2A-dependent manner. It is possible that a balance of different lysophospholipids released from apoptotic cells can affect migration.…”
Section: Steps Involved In Clearancementioning
confidence: 99%
“…Unlike LPC, other lysophospholipids or metabolic derivatives of LPC were unable to induce phagocyte chemotaxis. 24 This release of LPC was not simply leakage of cellular contents as the membrane integrity was intact. LPC release was dependent on caspase-3-mediated activation of calcium-independent phospholipase A2, 23 which hydrolizes membrane-lipid phosphatidylcholine.…”
Section: Steps Involved In Clearancementioning
confidence: 99%
See 1 more Smart Citation
“…Macrophage G2A Signaling-We have recently reported that lyso-PS can signal through the G proteincoupled receptor, G2A, for calcium flux (20), and G2A has been recently described as a receptor on macrophages responsible for mediating macrophage chemotactic responses (50,51). Accordingly, G2A appeared to be a reasonable candidate for lyso-PS-dependent enhancement of apoptotic cell engulfment.…”
Section: Lyso-ps Enhances Ps-dependent Engulfment Of Apoptotic Cells mentioning
confidence: 99%
“…These lipases produce numerous second messengers, including arachidonic acid for the synthesis of prostaglandins and leukotrienes to control inflammatory and immune responses, lysophosphatidylcholine to provide a chemotactic signal for macrophages and lymphocytes, and diacylglycerol for the activation of protein kinases (11)(12)(13)(14). Although it is known that the NTE1-encoded phospholipase B catalyzes the deacylation of PC to produce fatty acids and glycerophosphocholine, its cellular role is not known.…”
mentioning
confidence: 99%